Using integrated project-based and 4C-scaffolding (PJ4CS) to improve students' critical thinking skills - Hama, Ningsi Hi; Amin, Astuti Muh. (Inornatus: Biology Education Journal, 2025)
Critical thinking skills are the ability to interpret, reason, and evaluate information in order to make the right decisions. This study aims to analyze the effect of the Pj4CS (Integrated Project-Based and 4C-Scaffolding) learning model on students' critical thinking skills. This is a quasi-experimental study, with a Non-Equivalent Control Group Design. The research instrument includes valid and reliable critical thinking skills test questions. The results of the study showed a Sig. (2-tailed) value <0.05, so the research hypothesis was accepted. This means that there is a significant effect of the Pj4CS learning model on the critical thinking skills of class XI students at SMA Negeri 5 Kota Ternate. The Pj4CS model can be used by teachers as an alternative in strengthening students' critical thinking skills and preparing them to face the challenges of the 21st century. These results are expected to contribute to improving the quality of learning in the classroom.